2011
DOI: 10.1016/j.micinf.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Improved capacity of a monkey-tropic HIV-1 derivative to replicate in cynomolgus monkeys with minimal modifications

Abstract: Human immunodeficiency virus type 1 (HIV-1) hardly replicates in Old World monkeys. Recently, a mutant HIV-1 clone, NL-DT5R, in which a small part of gag and the entire vif gene are replaced with SIVmac239-derived ones, was shown to be able to replicate in pigtail monkeys but not in rhesus monkeys (RM). In the present study, we found that a modified monkey-tropic HIV-1 (HIV-1mt), MN4-5S, acquired the ability to replicate efficiently in cynomolgus monkeys as compared with the NL-DT5R, while neither NL-DT5R nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…McCarthy et al reported that H4/5L and helix 6 of SIVmac239 CA also affect TRIM5␣ sensitivity (55). In the construction process for our HIV-1mt clones, we found that the CA elements involved in the interaction with RhM TRIM5␣ are the CypA-binding loop within H4/5L, H6/7L, M94L/R98S within H4/5L, and Q110D/G114Q in helix 6 (18)(19)(20)56; this study). Of the substitutions identified in this study, R98S was the primary residue to increase TRIM5␣ resistance and improve viral growth in macaque cells.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…McCarthy et al reported that H4/5L and helix 6 of SIVmac239 CA also affect TRIM5␣ sensitivity (55). In the construction process for our HIV-1mt clones, we found that the CA elements involved in the interaction with RhM TRIM5␣ are the CypA-binding loop within H4/5L, H6/7L, M94L/R98S within H4/5L, and Q110D/G114Q in helix 6 (18)(19)(20)56; this study). Of the substitutions identified in this study, R98S was the primary residue to increase TRIM5␣ resistance and improve viral growth in macaque cells.…”
Section: Discussionsupporting
confidence: 65%
“…We and others have reported the construction of HIV-1 derivatives that have the ability to evade restriction factors for macaque model studies (16)(17)(18)(19)(20)(21). As a common feature, all reported macaque-tropic HIV-1 (HIV-1mt) clones have the vif gene, which can neutralize macaque APOBEC3G (e.g., SIVmac239 vif).…”
mentioning
confidence: 99%
“…To obtain a novel class of HIV-1 that infects, replicates and finally causes AIDS in macaques, we and a research group in USA have independently initiated the work on HIV-1mt and have done macaque model studies (Hatcho et al, 2008;Hatziioannou, 2006Kamada et al, 2006Kamada et al, , 2009Kuroishi et al, 2009;Nomaguchi et al, 2008a;Saito et al, 2011;Yamashita et al, 2008). Another group has published a report on HIV-1mt derivatives very recently (Thippeshappa et al, 2011).…”
Section: Generation and Characterization Of Various Hiv-1mt Clonesmentioning
confidence: 99%
“…On the basis of this strategy, we have successfully obtained a number of new generations with increasing ability to replicate from the original prototype NL-DT5R (see below). However, so far, none of the HIV-1mt clones tested are pathogenic for macaques (pig-tailed and cynomolgus) Nomaguchi et al, manuscript in preparation;Saito et al, 2011), although they all can replicate in the monkeys. The newest clones in Fig.…”
Section: Generation and Characterization Of Various Hiv-1mt Clonesmentioning
confidence: 99%
See 1 more Smart Citation